Canopy light signals and crop yield in sickness and in health : review article - Casal, Jorge José (2013)
Fil: Casal, Jorge José. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.